Gradual resumption on in-person classes - Office of the President - De La Salle University, Manila (Animo Repository, 2021)
For the new academic year, Br. Bernard S. Oca FSC shared the University’s plan for the gradual resumption of in-person classes as approved by the multi- sectoral committee on the resumption of face-to-face classes.